Process and impact of patient involvement in a systematic review of shared decision making in primary care consultations. (12th May 2016) - Hyde, Catherine; Dunn, Kate M.; Higginbottom, Adele; Chew‐Graham, Carolyn A.
Abstract: Background: Patient and public involvement and engagement (PPIE) in systematic reviews remains uncommon, despite the policy imperative for patient involvement in research. The aim of this study was to investigate the process and impact of collaborating with members of a patient Research User Group (RUG) on a systematic review about shared decision making around prescribing analgesia in primary care consultations. Methods: Five members of an established patient RUG collaborated with researchers undertaking a systematic review with narrative synthesis, through workshops held at three time‐points. These addressed the following: designing the protocol, interpreting the results and planning dissemination. Support from a RUG coordinator and user support worker facilitated collaboration throughout the review process. Researchers reflected on how PPIE modified the review at each time‐point. Results: RUG members identified factors important in shared decision making around analgesic prescribing additional to those initially proposed by the research team. Search terms and specific outcomes of interest were amended to reflect these additional factors. Thirty of the 39 patient‐identified factors were absent in the published literature. The categories of factors identified were used as a framework for the narrative synthesis and for reporting results. RUG members prioritized options for disseminating the results. Conclusion: PPIE collaboration throughout the systematic review impacted on the scope of the review, highlighting gaps in the literature that were important to patients. Impact on interpretation and dissemination of findings ensured the review directly reflected patient priorities. Challenges and strategies to facilitate PPIE involvement in systematic reviews and suggestions for future researchers are highlighted.